Integrative analysis of transcriptome and metabolome reveals the mechanism of foliar application of Bacillus amyloliquefaciens to improve summer tea quality (Camellia sinensis) - Huang, Xiangxiang (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.